ASISTENSI P5 SMA SINAR DHARMA DENGAN TEMA AUGMENTED REALITY - Carisha Puspa Gozali; Tiga Wira Prasidya; Darius Andana Haris (Jurnal Serina Abdimas, 2025)
Advanced technology has implemented many things, such as entertainment, health, and education. The birth of various innovations is motivated by the development of technology in this ongoing era. One of the technological developments that is quite influential is Augmented Reality, a technology that combines two-dimensional or three-dimensional virtual differences into a real environment. In connection with the government's policy regarding a program called the Pancasila Student Profile Strengthening Project or P5 with the theme "Engineering and Technology to Build the Republic of Indonesia", Augmented Reality (AR) technology is determined in the relevant school as the basis for making the project. This activity aims to further hone the abilities and skills of students in adapting to the advancement of technology in the 21st century by implementing their knowledge into AR-based learning media. With the background of informatics learning that has been obtained by students, the theme related to this technology is in accordance with the sustainability of the program. With this activity, it is expected to bring a positive impact to the educational life of students. Before this PKM, several similar PKMs had been implemented, one of which was a workshop and competition for making AR-based games. The implementation of PKM is divided into several stages: needs assessment, material development, and workshop implementation. The existence of this report proves that the activity went well, smoothly, and students succeeded in producing interactive AR-based learning media that is in accordance with the theme. Students also practice their ability to work in groups to hone their communication skills, with the hope that students are ready to go directly into society with diverse characteristics and ideas. ABSTRAK Teknologi maju telah mengimplementasikan banyak hal, seperti hiburan, kesehatan, maupun pendidikan. Lahirnya berbagai inovasi dilatarbelakangi dengan berkembangnya teknologi pada zaman yang sedang berlangsung ini. Salah satu perkembangan teknologi yang cukup berpengaruh adalah Augmented Reality, sebuah teknologi yang menggabungkan beda maya dua dimensi maupun tiga dimensi ke dalam suatu lingkungan nyata. Sehubungan dengan kebijakan pemerintah mengenai suatu program yang bernama Proyek Penguatan Profil Pelajar Pancasila atau P5 yang bertemakan “Berekayasa dan Berteknologi Untuk Membangun NKRI”, maka teknologi Augmented Reality (AR) ditetapkan pada sekolah yang bersangkutan sebagai basis dari pembuatan proyek tersebut. Kegiatan ini bertujuan untuk mengasah lebih dalam kemampuan dan keterampilan peserta didik dalam beradaptasi dengan majunya teknologi di abad ke-21 ini dengan mengimplementasikan pengetahuan mereka ke dalam sebuah media pembelajaran berbasis AR. Dengan latar belakang pembelajaran informatika yang pernah didapat oleh peserta didik, maka tema yang berkaitan dengan teknologi ini sesuai dengan keberlangsungan program. Dengan adanya kegiatan ini diharapkan agar dapat membawa dampak positif ke dalam kehidupan pendidikan peserta didik. Sebelum adanya PKM ini, sudah terlaksana beberapa PKM serupa, salah satunya adalah kegiatan workshop dan kompetisi pembuatan permainan berbasis AR. Pelaksanaan PKM dibagi dalam beberapa tahap: pengkajian kebutuhan, pengembangan materi, dan pelaksanaan lokakarya. Adanya laporan ini membuktikan bahwa kegiatan berjalan dengan baik, lancar, serta peserta didik berhasil menghasilkan media pembelajaran berbasis AR yang interaktif dan sesuai dengan tema. Peserta didik juga melatih kemampuan bekerja dalam kelompok untuk mengasah kemampuan komunikasi mereka, dengan harapan agar peserta didik siap untuk terjun langsung ke masyarakat dengan karakteristik dan ide yang beragam.